Detection of methicillin or multidrug resistant Staphylococcus aureus (MRSA) in locally produced raw milk and soft cheese in Baghdad markets - Kanaan, Manal Hadi Ghaffoori; AL-Shammary, Ali Hassan Ahmed (The Iraqi Journal of Veterinary Medicine, 2013)
In order to investigate the presence of methicillin or multidrug resistant Staphylococcus aureusin food-chain especially Cows raw milk and white raw soft cheese and its whey, a total of 30 samples were collected randomly from different markets in Baghdad Province during December 2012 till February 2013, in which samples were analyzed by a standard isolation protocols of food microbiology with some modification processing by new, modern and rapid technology tools such as chromogenic medium Baird-Parker agar, Electronic RapIDTM Staph Plus Code Compendium Panel System (ERIC®) Dryspot Staphytect Plus and Penicillin Binding Protein (PBP2’) Plus assays; as well as, studying the susceptibility of isolates to different selected antibiotics. The results profile showed isolation, identification, confirmation and enumeration of 10 (33.4%) isolates of MRSA as 4 (13.4%) isolates from raw milk and 6 (20%) isolates from white raw soft cheese with its whey. These findings suggest presence of MRSA type in locally produced raw milk and soft cheeses in Baghdad markets thus recommended to monitoring these products periodically to inshore public health.